Effect of aqueous extract of Ficus platyphylla on female Wistar rats with estradiol valerate-induced polycystic ovarian syndrome - Chinenye Jane Ugwah-Oguejiofor,; Shaibu Oricha Bello,; Raymond U Okolo,; Emmanuel U Etuk,; Michael Oguejiofor Ugwah,; Vincent Ugochukwu Igbokwe,; Mohammed Umar, (International Journal of Phytomedicine, 2014)
The aim of the study was to investigate the effects of Ficus platyphylla on female Wistar rats with estradiol valerate (EV)-induced polycystic ovarian syndrome (PCOS). PCOS was induced in female Wistar rats with regular 4-5 day oestrus cycles via the intramuscular injection of 4 mg EV per rat in an oily solution. The rats were allowed 30 days to establish PCOS. Then, the animals were divided into five treatment groups. The positive control group received clomiphene citrate, the negative control group received distilled water and the other groups received 100, 200 and 400 mg/kg of the aqueous extract. All groups were dosed for 15 days, except the positive control group, which was dosed for 5 days. On the 16th day, the animals were sacrificed. Hormonal assays and histological studies were then conducted. An elevated Luteinizing hormone (LH)-to- Follicle stimulating hormone (FSH) ratio is typical in many women with PCOS. The extract-treated groups showed a lower LH/FSH ratio compared with both the positive and the negative control groups. The progesterone levels were higher in the extract-treated groups compared with the negative control group, indicating luteal phase repair. The influence of the extract on ovarian morphology in the EV-induced PCOS model showed a marked reversal of polycystic ovary. These data help validate the use of this extract in folk medicine for the treatment of infertility. Considering its apparent safety, this study paves the way for an efficacy study for its use in treatment of PCOS in humans.